(untitled) (Annals of Medical Research, 2021)
Aim: Adrenomedullin (ADM) is a vasodilator, natriuretic and antiproliferative peptide that lowers blood pressure and inhibits cell migration. The expression of cardiac ADM is increased in heart failure (HF). The objective of this study was to investigate and simultaneously compare the levels of probrain natriuretic peptide (pro-BNP) and ADM as a potential marker in patients with HF.Material and Methods: In this study, plasma levels of probrain natriuretic peptide and ADM were investigated in 90 subjects with systolic heart failure and 90 healthy controls. The results were compared with appropriate statistical methods. Results: ADM levels were increased in patients with systolic HF with mean levels of 87.7 (81.4–99.7) pg/mL in HF group and 70.8 (65.2–78.7) pg/mL in healthy controls (p 0.001). Elevated ADM levels in HF were found to demonstrate a positive correlation with New York Heart Association (NYHA) functional classification (r = 0.94, p 0.001) and pulmonary arterial systolic pressure (PASP) (r = 0.44, p 0.001), and a negative correlation with left ventricular ejection fraction (LVEF) (r = -0.50, p 0.001) and creatinine clearance (GFR) (r = -0.21, p = 0.045). The area under the curve for HF was similar for ADM (1.00) and pro-BNP (1.00). Conclusion: The study showed that ADM may have a diagnostic value in indicating systolic HF. In addition, it was found that ADM levels increased with worsening HF and were positively correlated with NYHA class, pro-BNP and PASP, while ADM levels were negatively correlated with LVEF, GFR.